Evaluation of a Structuralized Sick-Leave Programme Compared with usual Care Sick-Leave Management for Patients after an Acute Myocardial Infarction - Lars Tjessum; Stefan Agewall (Journal of Rehabilitation Medicine, 2023)
Objective: To compare a structuralized sick-leave programme with usual care sick-leave management in patients after an acute myocardial infarction. We hypothesize that a structured sick-leave programme will yield a faster return to work without negatively affecting quality of life. Methods: Patients admitted to Oslo University Hospital due to an acute myocardial infarction were included in the study. Patients were randomized into an intervention group or a conventional care group. Patients randomized to the intervention group were provided with a standard programme with full-time sick leave for 2 weeks after discharge and then encouraged to return to work. The sick leave of the conventional group was mainly managed by their general practitioner. Results: A total of 143 patients were included in the study. The conventional care group had a mean of 20.4 days absent from work, while that of the intervention group was significantly lower, with a mean of 17.2 days (p < 0.001) absent. There was no significant change in quality of life between the groups. Conclusion: These findings strengthen the case for structuralized follow-up of patients with acute myocardial infarction, as this will have positive economic consequences for the patient and society as a whole, without making quality of life worse. Further investigation, with a larger study population, is warranted to determine the extent of health benefits conferred by early return to work.